Clinical Implications of Dental Injury Analysis in Forensic Odontology: A Review Article - Khan, Muhammad S.; Suhartono, Antonius W.; Auerkari, Elza I. (e-GiGi, 2025)
Abstract: Dental trauma is a common occurrence in forensic investigations and may provide important clues about the amount of damages and when they occurred, both of which are vital in court cases. Forensic pathologists and dentists work hand in hand to assess and diagnose oral injuries accurately, which is crucial for those who are alive and those who have passed away. In order to guarantee accurate forensic results, the need of standardizing procedures used in dental trauma analysis, such as clinical and radiographic tests, and the need of thorough documentation are very crucial. The many kinds of dental injuries, their causes, and how forensic applications help to identify victims and piece together are very important to be discussed. This article provides a comprehensive overview of the importance of dental injury analysis, procedures and their implications in various cases within the scope of forensic odontology for efficient practice, highlighting the vital role of forensic odontology in medico-legal investigations via an in-depth review of the existing literature. Keywords: dental trauma; forensic odontologist; clinical examination; radiographic assessment; legal context